MOTIVATION AND SELF-REGULATION OF ENGLISH STUDY PROGRAM STUDENTS IN ONLINE LEARNING - Rosina Lekawael; Pricilia Tupalessy; Afiliani -; Imanuel P. Ch Tomasoa (Faculty of Teacher Training and Educational Sciences, Pattimura University Indonesia, 2023)
Motivation for online learning is decreased in the past pandemic virus Covid-19. For this reason, self-regulation plays an important role in order to control students’ thoughts and feelings in achieving learning goals. Motivation and self-regulation are aspects necessary in the English learning process. This study was conducted to find out the factors affecting students’ motivation and self-regulation toward online learning. A descriptive qualitative method was used to explain the phenomena through an interview by using open-ended questions to 10 students as a representation. The result shows that there are seven significant elements that give motivational and self-regulated effects to them toward online learning; objectives, task strategy, time management, help-seeking, teaching presence (homogeneous instructional design: structure and layout of OL platforms), interest, and competence. Self-regulation is essential to direct and regulate students’ cognitive processes during online learning. For sure, both cannot be separated from students’ daily life. These attract the attention of the lecturers to the fact that students are not only language receivers but persons with hearts, feeling, and identities. Students and lecturers should work together to integrate those things to achieve successful English learning goals.